Does mangrove restoration imply coastal protection? A prospective simulation study - Juanico, Drandreb Earl O. (Frontiers in Marine Science, 2022)
Mangrove restoration in the coastal zones is a concept proposed by environmental conservationists. Among the cited advantages of mangrove restoration are providing socio-economic services and coastal protection. Aware of these advantages, countries in Southeast Asia, such as the Philippines, have been implementing government- or civilian-backed restoration efforts. However, will current practices of restoration lead to the intended results? Also, are claims of coastal protection effects realistic? These two questions underscore the challenges posed by the long gap between the present intervention and future impact. Field evidence of protection may emerge from existing sites, the circumstances of which may not be easily portable onto other sites. This study examines the mangrove restoration practices in the Philippines and proposes the restoration index as a short-term prospective estimate of the future success of the restoration effort. This study also assesses the coastal protection potential of mangroves by examining the “bio-shielding” effect against storm surges driven by category-5 winds. Two coastal sites—Tacloban, Leyte, and Pan de Azucar, Iloilo—in the Philippines along the track of a category-5 storm, were considered. The restoration index was calculated based on the characteristics of Rhizophora mangroves commonly used in restoration programs. The coastal inundation model examined the extent of inland flooding due to storm surges by comparing an actual and hypothetical mangrove scenario for each site. A reasonable value of tree density obtained from the restoration simulations was estimated to determine if and to what degree, do mangroves in both sites offer coastal protection. For Tacloban, the actual mangroves are limited in scope, while the hypothetical scenario assumed a mangrove greenbelt fringing the city’s eastern periphery. For Pan de Azucar, the existing mangroves are dense at the southwestern tip of the island, whereas in the hypothetical scenario, these mangroves are absent. The results, reinforced with a household survey, indicated a positive economic value of mangrove restoration for coastal protection. The restoration index and coastal inundation simulations are prospective tools that will guide the Philippines and Southeast Asia, in general, in formulating impactful mangrove restoration programs.